Votive offering of coins in the waters: the case of the Anna Perenna fountain in Rome (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2024)
The contribution wishes to present, in an introductory and synthetic manner, the main features that distinguished the offering of money in the waters and the diffusion of this specific devotional form in the Roman-Imperial age, starting from the offerings, numismatic and otherwise, found in Anna Perenna’s spring in Rome. The fountain, excavated as part of an emergency archaeology intervention by the Soprintendenza Archeologica di Roma between November 1999 and January 2000, makes it possible to delineate a specific devotional and religious framework from the imperial age to the late antique period, and testifies to a transformation of the specific aspects of the cult of Anna Perenna over time. The presence of coins in the source, although published in a synthetic and incomplete manner, also makes it possible to better identify the evolution of the cult of Anna Perenna over the centuries.
Keywords: Anna Perenna; coin; Rome; Nymphs